Payment System Service Quality Analysis Qris Uses The Servqual Method at The Café Trilogi - Pemi Afely Athin; Surya Ade Saputra (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The development of digital payment systems has encouraged culinary business actors to adopt the Quick Response Code Indonesian Standard (QRIS) as an alternative to faster, practical, and more efficient transactions. However, the success of QRIS implementation is not only determined by its level of use, but also by the quality of service perceived by customers. This study aims to analyze the service quality of the QRIS payment system at Cafe Trilogi based on the gap between customer perception and expectations using the Service Quality (SERVQUAL) method. The study used a descriptive quantitative approach involving 100 respondents selected through purposive sampling techniques, namely Cafe Trilogi customers who had made transactions using QRIS. Data was collected through the distribution of questionnaires that had met the validity and reliability tests, then analyzed using SERVQUAL Gap Analysis on five dimensions of service quality, namely tangible, reliability, responsiveness, assurance, and empathy. The results showed that the quality of QRIS services at Cafe Trilogi obtained a positive gap value of +1.42, indicating that the services provided have met customer expectations. The assurance dimension had the highest gap value (+0.72), while the reliability dimension showed a negative gap (-0.01), indicating room for improvement in service consistency and network stability.